High-birefringence nematic liquid crystal for broadband THz applications. Issue 7 (27th May 2016) - Li, Xuefeng; Tan, Nicholas; Pivnenko, Mike; Sibik, Juraj; Zeitler, J. Axel; Chu, Daping
ABSTRACT: Liquid crystals (LCs) have been studied extensively in the visible range for their dielectric tunability, and the characterisation in the terahertz (THz) range has gained increasing interest due to the need for active THz modulation and switching devices. In this paper, we use THz time-domain spectroscopy to measure the frequency-dependent birefringence and the absorption coefficient of a number of commercial and non-commercial nematic LCs, including E7, BL037, MDA-98-1602, LCMS-107, GT3-23001 and 1825, over a range of bias voltages at room temperature. Furthermore, several basic components of LC mixture are analysed to establish their contributions to birefringence and theoretical model is used to fit the absorption spectra. The large tunability and low loss measured for a range of samples show that the LCs are useful tunable dielectrics for compact, efficient and broadband THz devices. GRAPHICAL ABSTRACT: